2017
DOI: 10.1039/c7cc03478d
|View full text |Cite
|
Sign up to set email alerts
|

A mechano-responsive supramolecular metal–organic framework (supraMOF) gel material rich in ZIF-8 nanoplates

Abstract: We report an unconventional ZIF-8 based supramolecular MOF (supraMOF) material, which is straightforwardly synthesised by leveraging the high concentration reaction (HCR) approach. Akin to traditional low-molecular-weight gels (LMWG), we show that mechano-stimulus responsive behaviour can be achieved through a reversible and fast sol-gel conversion mechanism. Remarkably, the supraMOF gel consists of 2D nanoplates of ZIF-8 with a reduced crystal symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Recent studies have shown that certain MOFs can be formed into freestanding gels that can be easily shaped, and then dried to form very dense monoliths. 18 In the present work, we initially discovered that certain known MOF gels (in particular HKUST-1 gel-TEA 13 and ZIF-8 19 ) had ideal characteristics as DIW inks (SI section 1), enabling us to 3D print freely shaped MOF monoliths. However, the synthesis of these gels required hazardous chemicals (dimethylformamide, DMF, and triethylamine, NEt 3 ) that were retained in the monoliths.…”
mentioning
confidence: 88%
“…Recent studies have shown that certain MOFs can be formed into freestanding gels that can be easily shaped, and then dried to form very dense monoliths. 18 In the present work, we initially discovered that certain known MOF gels (in particular HKUST-1 gel-TEA 13 and ZIF-8 19 ) had ideal characteristics as DIW inks (SI section 1), enabling us to 3D print freely shaped MOF monoliths. However, the synthesis of these gels required hazardous chemicals (dimethylformamide, DMF, and triethylamine, NEt 3 ) that were retained in the monoliths.…”
mentioning
confidence: 88%
“…[4][5][6] As a representative example, piezofluorochromic materials with pressure-dependent photoluminescence (PL) tuning properties are of great importance in such fields as mechanical sensors, security papers, data processing, storage devices, and so on. [7][8][9][10][11] However, traditional piezofluorochromic materials often suffer from problems concerning sensitivity, reversibility, tunability, and controllability, as well as a tendency to lose crystallinity and/or fluorescence, thereby deterring in-depth study of the mechanism and real applications. [12][13][14][15] In the last decades, metal-organic frameworks (MOFs) have emerged as a new class of multi-functional materials, [16][17][18] showing great potential in many fields including optoelectronics, [19][20][21] magnetics, [22][23][24] gas storage and separation, [25][26][27] heterogeneous catalysis, 28 drug delivery, [29][30][31][32][33][34][35] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 However, the deliberate design and synthesis of piezofluorochromic MOFs remain in their infancy. 7,11,14 In principle, tunable and controllable piezofluorochromism may be induced in MOFs by arranging mechano-responsive organic linkers into welldefined coordination frameworks to control the photophysical processes among…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystals of ZIF-8 were synthesized in dimethylformamide (DMF) under ambient conditions (Scheme 2a), as reported. 26 DMF and Et3N were purchased from Sigma Aldrich and used without further purification. Zn(NO3)2•6H2O and 2-mIm were purchased from Oakwood Products Inc. and used after recrystallization.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[23][24][25] During the last several years, the development of methods based on supramolecular chemistry has allowed for in situ self-assembly of ZIF-8 in the presence of amine modulators. 26 In particular, in situ and post-synthetic modification of ZIF-8 crystals by amine functionalization has resulted in tunable adsorption for specific applications in chemical sensing, 27 energy storage 25 and sequestration, 28 and catalysis 29 without significantly altering crystal structure, size, and morphology.…”
Section: Introductionmentioning
confidence: 99%